3D SEISMIC DATA INTERPRETATION TO IDENTIFY HYDROCARBON PRESENCE IN WELLS 25-1-X-14 AND 64-JX-15 USING SWEETNESS ATTRIBUTE IN TEAPOT DOME FIELD, WYOMING - Fauziyah, Ummi; Adhi, M. Aryono; Hardyanto, Wahyu (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2025)
Exploration activities in Teapot Dome can be carried out by looking at the geological structure. Determination of geological structure can be done by interpreting seismic data. This study aims to identify hydrocarbon prospect zones in the Teapot Dome field through 3D seismic interpretation of wells 25-1-X-14 and 64-JX-15, and to evaluate the application of sweetness and RMS amplitude attributes in determining the geological structure of the Teapot Dome using 3D seismic reflection data. The data interpretation processing stage starts from performing wavelet extraction, well seismic tie, horizon picking, and time structure map. This research utilizes seismic sweetness and RMS amplitude attributes with amplitude values of 10 to 60ms to map hydrocarbon distribution. The results of this study show that the greatest hydrocarbon distribution occurs at both markers in well 25-1-X-14, with amplitude values of 50 ms and 20 ms, indicated by the presence of sweet spots and bright spots. In well 64-JX-15, sweet spots and bright spots are observed at the top marker with an amplitude value of 20 ms. The application of attributes in determining the geological structure in the Teapot Dome field is found to be an anticline that runs from the northwest to the southeast.